The course of neuropsychological impairment and brain structure abnormalities in psychotic disorders. (January 2016) - Woodward, Neil D.
Highlights: Cognitive impairment and brain structure abnormalities in psychosis are reviewed. Pathways leading to brain dysfunction appear to differ between disorders. Brain dysfunction is present prior to illness onset in schizophrenia, but static thereafter. There is evidence of progressive cognitive decline in psychotic bipolar disorder. Longitudinal studies are required to better elucidate pathways of brain dysfunction. Abstract: Neuropsychological impairment and abnormalities in brain structure are commonly observed in psychotic disorders, including schizophrenia and bipolar disorder. Shared deficits in neuropsychological functioning and abnormalities in brain structure suggest overlapping neuropathology between schizophrenia and bipolar disorder which has important implications for psychiatric nosology, treatment, and our understanding of the etiology of psychotic illnesses. However, the emergence and trajectory of brain dysfunction in psychotic disorders is less well understood. Differences in the course and progression of neuropsychological impairment and brain abnormalities among psychotic disorders may point to unique neuropathological processes. This article reviews the course of neuropsychological impairment and brain structure abnormalities in schizophrenia and bipolar disorder.